STUDY OF GUSTATORY AND STRUCTURAL PROPERTIES OF KEFIR PRODUCT - MILENA H. MOMCHILOVA; GERGANA B. IVANOVA; AKSENIYA ATANASOVA; NEVENKA RUMYAN; NELLY V. GEORGIEVA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The subject of the study is the improvement of Kefir culture. For this investigation it was used Kefir culture and two series of experiments were carried out. Yeasts from probiotic strain Saccharomyces boulardii were added in the first series and the lactic acid bacteria (LAB) of Streptococcus thermophilus strain, with a polysaccharide activity were added to Kefir culture in the second series. The fermentation conditions were 30°C, duration 16 hours and cooling 4 hours up to 4°C. The characteristics of Kefir were analyzed by determination of: pH, acidity, qualitative reaction for existence of diacetyl, cell number of LAB and yeasts. The structural properties of Kefir were evaluated by microscopic study.